NEOFEUDALIZATION IN UKRAINE: CAUSES AND AFTERMATH - Пояркова, Т. К.; Зленко, Н. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article studies the main sings of neofeudalism: construction of hierarchical structures based on personal devotion of those who parasitize, using the monopolistic usage of the state’s rent; access to political activity and to promotion by means of origin or personal devotion to influential outfit; absolute power of local lords and elite clans. The author emphasizes the new neofeudal features connected with Russian-Ukrainian military involvement: creation and under the law activity of private armies, territorial battalions and self-defense detachments. Different conceptions of modern wars are analyzed: conflicts of low intensity, «new», hybrid, information wars. The article proves that neofeudalism is the aim of globalised epoch. The opinion that neofeudal tendencies in Ukraine and their spreading threaten the nation state is substantiated.